2019
DOI: 10.1002/term.2941
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐based scaffold counteracts hypertrophic and fibrotic markers in chondrogenic differentiated mesenchymal stromal cells

Abstract: Cartilage tissue engineering remains problematic because no systems are able to induce signals that contribute to native cartilage structure formation. Therefore, we tested the potentiality of gelatin‐polyethylene glycol scaffolds containing three different concentrations of chitosan (CH; 0%, 8%, and 16%) on chondrogenic differentiation of human platelet lysate‐expanded human bone marrow mesenchymal stromal cells (hBM‐MSCs). Typical chondrogenic (SOX9, collagen type 2, and aggrecan), hypertrophic (collagen typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
(89 reference statements)
0
18
0
Order By: Relevance
“…Therefore, "hPL should be considered a product category and not a single product" in which it is important to distinguish "essential" from "non-essential" content based on the intended application (Henschler et al, 2019). We have previously reported that our hPL4c A18 batch does not induce hMSC chondrogenic differentiation when used alone, but it exerts an inhibitory effect when used in combination with a specific chondrogenic differentiation medium containing TGFβ3 (Manferdini et al, 2019). It has been reported that the composition of hPL can induce hMSC to release cytokines affecting their proliferative and differentiative potential (Mathews et al, 2014;Karlsen and Brinchmann, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, "hPL should be considered a product category and not a single product" in which it is important to distinguish "essential" from "non-essential" content based on the intended application (Henschler et al, 2019). We have previously reported that our hPL4c A18 batch does not induce hMSC chondrogenic differentiation when used alone, but it exerts an inhibitory effect when used in combination with a specific chondrogenic differentiation medium containing TGFβ3 (Manferdini et al, 2019). It has been reported that the composition of hPL can induce hMSC to release cytokines affecting their proliferative and differentiative potential (Mathews et al, 2014;Karlsen and Brinchmann, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained by aggrecan transcript quantification in AT-hMSC cultured in OM, even if with low statistical significance. The negative impact of hPL on chondrogenic differentiation of hMSCs cultured in 3D Hydrogel-chitosan scaffolds was previously described [34] and it is probably due to the presence of cell receptor-binding competitors within hPL. On the other hand, the quantified adipogenic marker presents the opposite behavior to the different stimuli: statistically significant differences were observed only in AT-hMSCs, as expected, while no differences came to light by FABP4 transcript quantification in BM-hMSCs.…”
Section: Discussionmentioning
confidence: 71%
“…Chitosan is a biomimetic, biodegradable, biocompatible, non-immunogenic, and versatile polymer presenting appropriate mechanical strength and anti-bacterial properties [ 16 ]. It is also able to support growth factor activity [ 32 , 34 ]. For these reasons, chitosan is used in tissue engineering, production of artificial organs, biotechnologies, and for the regeneration of damaged tissues [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, gelatin and chitosan have been extensively used for tissue engineering applications, since they are biocompatible, biodegradable, non-antigenic, non-toxic and present antimicrobial activity [6,7]. Starting from this evidence and aiming to regenerate bone, recent literature has provided examples of optimized combinations of these materials to realize hybrid hydrogel scaffolds, presenting a structure that mimics native ECM constituents and reporting morphological and mechanical properties suitable to support cell growth, osteo-differentiation and mineralization [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%